Expression of Sclerostin in Osteoporotic Fracture Patients Is Associated with DNA Methylation in the CpG Island of the SOST Gene - Yanming Cao; Bin Wang; Ding Wang; Dongxiang Zhan; Caiyuan Mai; Peng Wang; Qiushi Wei; Yamei Liu; Haibin Wang; Wei He; Liangliang Xu (International Journal of Genomics)
Purpose. SOST gene is one of the key factors in regulating bone absorption. Although there are reports showing diverse transcription factors, epigenetic modification could be responsible for regulating SOST gene expression. There is still little exploration on promoter methylation status of SOST gene in osteoporotic bone tissues. The aim of this study is to investigate the involvement of CpG methylation in regulation of SOST expression in patients with primary osteoporosis. Methods. The diagnosis of osteoporosis was established on the basis of dual energy X-ray absorptiometry to measure BMD. All femoral bone tissues were separated in surgeries. After extracting total RNA and protein, we checked the relative expression levels of SOST by quantitative real-time PCR and western blot. Also, immunohistochemical staining was performed to observe the expression of SOST protein in the bone samples. The genomic DNA of non-OPF (non-osteoporotic fracture bone tissues) and OPF (osteoporotic fracture bone tissues) were treated by bisulfite modification, and methylation status of CpG sites in the CpG island of SOST gene promoter was determined by DNA sequencing. Results. SOST gene expression in the non-OPF group was lower than that in OPF group. Bisulfite sequencing result showed that SOST gene promoter was slightly demethylated in the OPF group, as compared with non-OPF group. Conclusion. Our study demonstrated that DNA methylation influenced the transcriptional expression of SOST gene, which probably may play an important role in the pathogenesis of primary osteoporosis.